Chapter "I nostri contadini solevano istare molto meglio per lo addrieto che ora": mezzadria, proprietà cittadina e disuguaglianza economica in Toscana, sec. XV-XVI - Cristoferi, Davide (Datini Studies in Economic History, 2020)
This paper studies through a quantitative analysis at micro-scale (the pieve of San Giovanni in Petroio in Mugello) in 1427-1512 the relation between the growing economic inequality of the Florentine rural society found by recent research and a peculiar share-cropping system, the mezzadria. By focusing on the mechanisms of wealth redistribution of this system, the paper suggests the role of mezzadria whether in increasing in the long-run the concentration of land property and in providing for the poorest social layers of rural population at subsistence level. In this regard, the paper contributes to explore the role of institutions in increasing wealth concentration from Middle Ages to the Early Modern times.